LEGAL FRAMEWORK OF THE EU POLICY IN THE FIELD OF DEFENCE SPACE TECHNOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The defence policy of the European Union is a reference point for development of legislation at supranational level that sets new dimensions for European integration. Maintaining a high-tech defence industrial base is among the key objectives that the Union sets itself in its security and defence policy. In this sense, a European defence policy focuses on cooperation between states to build, develop and upgrade the entire spectrum of land, air, sea and space defence capabilities. "Space is a strategic benefit essential to Europe's independence, security and prosperity." Space as a distinct operational area is of essential importance for the EU defence. Тhe policies of the Union are aimed both at ensuring independent and autonomous access to outer space and development of various types of defence technologies. That will best enable rapid situational awareness, rapid decision-making and efficient operations. The space defence technology infrastructure established by the EU should meet the security needs of the Union. Based on this, the EU legal framework on space as a separate area of security and defence reveals different types of supranational legal instruments. They regulate specific military and political issues regarding space defence and technology development.